Social Interaction as a Determinant of Social Psychological Well-Being - Ilham, Muhammad; Abdillah, Reza; Ariyadi, Agus (Journal Social Humanity Perspective, 2025)
Social interaction is a key predictor of social psychological wellbeing in the development and retention of social psychological wellbeing, and social interaction is related to identity construction processes, affective belonging, and emotional resilience maintenance. The current qualitative study evaluates how everyday interaction in familial, peer, community, and workplace situations contribute to the psychological well-being or whether it suppresses it. The collection of the data was performed through the in-depth semi-structured interviews with twenty participants, which were complemented by the field notes and observed using the thematic analysis to identify the patterns and relational dynamics that are common. Findings show that positive exchanges bring about emotional affirmation, strengthen self-esteem, and foster the feeling of belonging but displays the negative impact of barriers to well-being social exclusion, conflict, cultural incongruence, and time. As noted repeatedly by the participants, affirmative engagement in the social realm strengthens individual identity and group membership, thus, demonstrating a psychological well-being as an interpersonal construct that is mutually formed during meaningful social interactions. Organizationally, these outcomes support the strategic significance of relational environments, meaning that institutions and societies should emphasize the need to engage in inclusive, participatory and supportive relationships to increase employee engagement, shared cohesiveness, and overall performance. The current research becomes an element of the integration of social psychology and management literature because it shows that the concept of well-being involves more than personal qualities to include social and organizational factors. The practical findings offer practical information to leaders, policy makers, and organizational structure designers, who aim at fostering an environment that helps promote resilience, trust, and human flourishing. Together, this body of study highlights social interaction as both a humanistic and strategic determinant of well-being and its centrality in maintaining identity, belonging and relational harmony.